Effects of postural taping on pain, function and quality of life following osteoporotic vertebral fractures—A feasibility trial. (28th May 2018) - Palmer, Shea; Barnett, Sue; Cramp, Mary; Berry, Alice; Thomas, Amanda; Clark, Emma M.
Abstract: Objective: Osteoporotic vertebral fractures (OVFs) are common and present a significant burden to patients and healthcare services. Poor posture can increase vertebral pressure, pain and the risk of further fractures. The aim of the present study was to investigate the effects of postural taping on pain, function and quality of life when used in addition to usual care. Methods: A feasibility randomized, controlled trial was carried out in men and women with at least one clinically diagnosed painful OVF. Participants were randomly allocated to use an adhesive postural taping device at home for 4 weeks or to continue with usual care. Outcomes assessed at baseline and 4 weeks included pain at rest and on movement (visual analogue scales [VASs]), and function and quality of life (Quality of Life Questionnaire of the European Foundation for Osteoporosis [QUALEFFO]). Health resource use and acceptability were explored using a specifically designed questionnaire. Results: Twenty‐four participants completed the trial (taping, n = 13; control, n = 11). Groups were comparable in age, although the control group contained more men ( n = 3 versus n = 0) and scored slightly lower on most outcome measures at baseline. Descriptive analysis favoured the taping group for most outcome measures. Effect sizes were small to medium (0.37, 0.45 and 0.66 for VAS rest, VAS movement and QUALEFFO, respectively). Conclusions: The taping device demonstrated potential to improve pain and function. However, the findings need to be replicated in an appropriately powered study. The study procedures were largely acceptable. A more extensive pilot trial is recommended prior to a definitive trial.